Consulting report – Café Comadre - Balbina Gistel, Jasmin; Alcantara Sepulveda, Joan Manuel; Pallari, Patrik Mikael (Pontificia Universidad Católica del Perú, 2023)
This consulting report is a comprehensive analysis of Café Comadre, a coffee establishment located in Pueblo Libre, which has a dual-pronged mission of empowering Peruvian coffee farmers and promoting sustainability coffee consumption. The consulting project extensively explores various aspects of the café's operations, including its strengths, weaknesses, opportunities, and threats, shedding light on the significance of its decentralized supply network and its alignment with prevailing sustainability trends within the industry. The analysis reveals key challenges faced by Café Comadre, notably in the domains of resource management and human resources. These challenges are identified as impediments to the café's growth and sustainability objectives. To address these challenges and capitalize on its strengths, the consulting thesis offers a set of comprehensive and actionable recommendations. These recommendations encompass waste reduction strategies, leadership workshops to enhance managerial skills, forging strategic sustainability partnerships, and implementing robust customer service training programs. The thesis also underscores the imperative of fostering a culture of continuous learning within the organization. By diligently executing these strategic initiatives, Café Comadre aspires to carve a distinct and enduring niche in the highly competitive coffee market. These endeavors are meticulously aligned with the café's overarching mission and vision, which are firmly rooted in growth, sustainability, and the pursuit of operational excellence. In sum, it serves as a strategic roadmap for Café Comadre, outlining a path towards realizing its dual mission and vision, thereby reinforcing its position as a responsible and sustainable player in the dynamic coffee landscape.

Este informe de consultoría es un análisis exhaustivo de Café Comadre, un establecimiento de café ubicado en Pueblo Libre, que tiene como misión empoderar a los agricultores de café peruanos y promover la sostenibilidad. El proyecto de consultoría explora en profundidad varios aspectos de las operaciones del café, incluyendo sus fortalezas, debilidades, oportunidades y amenazas, principalmente sobre la importancia de su red de suministro descentralizada y su alineación con las tendencias de sostenibilidad prevalecientes en la industria. El análisis revela los principales desafíos enfrentados por Café Comadre, especialmente en los ámbitos de gestión de recursos y recursos humanos. Estos desafíos se identifican como obstáculos para los objetivos de crecimiento y sostenibilidad del café. Para abordar estos desafíos y aprovechar sus fortalezas, la tesis de consultoría ofrece un conjunto de recomendaciones exhaustivas y viables. Estas recomendaciones abarcan estrategias de reducción de desperdicios, talleres de liderazgo para mejorar las habilidades directivas, forjar alianzas estratégicas de sostenibilidad e implementar programas sólidos de capacitación en servicio al cliente. La tesis también destaca la importancia de fomentar una cultura de aprendizaje continuo dentro de la organización. Mediante la ejecución de estas iniciativas estratégicas, Café Comadre aspira construir una marca sustentable y ser altamente competitivo dentro del mercado del café. Estos esfuerzos están alineados con la misión y visión globales del café, que están firmemente arraigados en el crecimiento, la sostenibilidad y la búsqueda de la optimización de recursos. En resumen, este informe sirve como una hoja de ruta estratégica para Café Comadre, delineando un camino hacia la realización de su misión y visión duales, reforzando así su posición como una cafetería responsable y sostenible en el dinámico panorama del café.
Keywords: Consultores de empresas--Planificación estratégica; Café--Industria y comercio--Perú; Cafeterías--Administración--Perú--Pueblo Libre (Lima : Distrito); https://purl.org/pe-repo/ocde/ford#5.02.04